RESEARCH NOTES: THE ANTECEDENTS AND CONSEQUENCES OF UNION COMMITMENT: A META-ANALYSIS. - Bamberger, Peter; Kluger, Avraham N.; Suchard, Ronena (Academy of Management Journal, 1999)
We tested three published models of union commitment’s antecedents and consequences as well as an integrative model, using correlation coefficients derived from 15 meta-analyses of five union commi...